Against Legitimacy - James, Matt (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2012)
Francis Dupuis-Déri confronts the domestication of radical ideas in his superb and stimulating essay, “Global Protestors Versus Global Elites: Are Direct Action and Deliberative Politics Compatible?”, and leads to the intriguing claim that the legitimacy of radical anti-capitalist protest rests ultimately on its internally deliberative quality. This account, however compelling as it stands in many ways, seems to give undue predominance to legitimacy claims. The problem of democracy and global capitalism today is that the global justice movement’s designated constituency does not exist as an actor, for the simple reason that the majority of its putative members have yet to accept the problem forwarded by the global justice movement. People must be convinced to join movements against corporate control, democratic weakening, and income inequality ; fortifying legitimacy among the already committed does not seem to be helping.